Further Validation of the Multidimensional Fatigue Symptom Inventory-Short Form - Stein, Kevin D. (2004)
A growing body of evidence is documenting the multidimensional nature of cancer-related fatigue. Although several multidimensional measures of fatigue have been developed, further validation of these scales is needed. To this end, the current study sought to evaluate the factorial and construct validity of the 30-item Multidimensional Fatigue Symptom Inventory-Short Form (MFSI-SF). A heterogeneous sample of 304 cancer patients (mean age 55 years) completed the MFSI-SF, along with several other measures of psychosocial functioning including the MOS-SF-36 and Fatigue Symptom Inventory, following the fourth cycle of chemotherapy treatment. The results of a confirmatory factor analysis indicated the 5-factor model provided a good fit to the data as evidenced by commonly used goodness of fit indices (CFI 0.90 and IFI 0.90). Additional evidence for the validity of the MFSI-SF was provided via correlations with other relevant instruments (range −0.21 to 0.82). In sum, the current study provides support for the MFSI-SF as a valuable tool for the multidimensional assessment of cancer-related fatigue.